Subject Predicate and Focus Marking in Isinay - Constantino, Ernesto (The Archive; Vol 4 (1984): Publication Four: Studies on Philippine Minor Languages, 2025)
The paper is concerned with subject, predicate and focus marking in the Isinay language. The data used in this study comes from the dialect of Isinay spoken in the town of Dupax, Nueva Vizcaya. This study aims to show the different ways of marking the three said grammatical functions in the Isinay language based on the use of markers. The examples used in this paper are simple verbal sentences with a subject and a predicate.